ENDOVASCULAR TREATMENT OF A JUXTARENAL AORTIC ANEURYSM WITH THE CHIMNEY TECHNIQUE - Gouveia e Melo, Ryan (2017)
Endovascular treatment of juxtarenal aortic aneurysms is a complex challenge to the vascular surgeon. We present a case of an 83 year old man with a large juxtarenal aneurysm treated with an endovascular approach with chimneys to the left renal artery and superior mesenteric artery. Fenestrated aortic endovascular repair has been considered the preferred endovascular approach in juxtarenal aneurysms, however when the risk of rupture is considered high to wait for a manufactured device and/or when the anatomy is not suitable for a fenestrated repair, chimney endovascular repair is a viable and promptly available option.  This case report is an example of the applicability of this treatment with a positive short-term outcome as shown here.